Untangling the Knot: A Causal Analysis Model of Child Marriage in Aceh - Ramadhani, Putri; Marzaniar, Putri; Muazzinah, Muazzinah (Al-Ijtima`i: International Journal of Government and Social Science, 2025)
Child marriage is a complex social issue that requires serious attention in Aceh, especially in Bener Meriah Regency. This study aims to analyze the factors causing child marriage and its impact on individuals and society. This study uses a mixed method approach. The results confirm that the factors causing child marriage are socio-cultural factors, media exposure, and sexual education. Socio-cultural factors are evident in the high correlation between child marriage and the community environment, such as economics, education, culture, society, and peer influence. Media exposure also contributes to encouraging children's freedom in accessing and using social media without restrictions from parents, and low comprehensive sexuality education due to the “sumang” culture also hinders the delivery of comprehensive sexuality education and knowledge to children and the community. Thus, this study is expected to contribute to efforts to prevent child marriage and raise public awareness about the importance of child protection and the fulfillment of children's rights.